Animated Video Based on Scientific Approach for Science Content: Changing Energy Forms Material for Class IV - Intan Fakhriyyah; Ni Wayan Suniasih; Didith Pramunditya Ambara (Jurnal Pedagogi dan Pembelajaran, 2025)
Science learning that lacks student involvement can become boring. Engaging media is needed to boost interest and make the process more interactive. This study aims to prove the effectiveness of animated video learning media based on a scientific approach to the content of science subjects on changing energy forms for grade IV students. The type of research conducted is development research using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The subjects of the study were 32 grade IV students. The data collection method used questionnaires, tests, and the instruments used were questionnaire sheets and multiple-choice tests. The data analysis technique used quantitative descriptive analysis and inferential statistical analysis. The results of the effectiveness test obtained tcount = 5.79 for a significance level of 5% = 0.05. This means that tcount> ttable, which means H0 is rejected and H1 is accepted. This means that there is a significant difference (5%) after using the product. The increase in the average student score can be seen based on the students' answers when answering the test questions given. Most students. It can be concluded that, animated videos based on scientific approaches are effectively applied to the content of science subjects on changing energy forms for grade IV. The implications of this study are expected to be an example for teachers in conducting learning using learning video media. Thus, the innovation of animated videos based on scientific approaches can prevent students from getting bored in learning.